Waist Circumference: An Important Marker for Hypertension - Sanam Anwar; Hajir H Rashid; Ghadeer J Moslhey; Bushra Aleem (Medsci Publications, 2019)
Introduction: High blood pressure indirectly identified through anthropometric indicators may be an efficient strategy for detection and control, mainly because these measures can be implemented without specialized technical apparatus. The study was done with the objective of evaluating waist circumference as marker for hypertension. Methods: Blood pressure, height, weight and waist circumference was measured using standard procedures for all participants in the cross sectional study. t test and ANOVA test was used to compare mean values of waist circumference among different groups. Results: There was a statistically significant difference in waist circumference between age groups (F = 4.388, p=0.013); education groups (F = 11.037, p=0.000) and BMI groups (F = 57.7, p=0.000). 63.5% of hypertensive had waist circumference more than the gender specific cutoff point. Both mean systolic and diastolic blood pressure was higher in the individuals with waist circumference more than the gender specific cutoff for all the categories of BMI in both the genders. The proportion of hypertensive was 45.5% in normal weight and 57.4% in overweight group with waist circumference more than gender specific cutoff (p<0.05). Conclusion: The study emphasizes the need for using simple anthropometric tool like waist circumference for assessing risk of hypertension in communities.